O entre-lugar das artes cênicas no espetáculo "Coreografia de cordel" da Cia. de Dança do Palácio das Artes: Um Olhar Expressivo Sobre Coreografia de Cordel - Talitha de Castro Mendonça Mesquita (2015)
This text presents a look at the disciplinary relationships between scenic arts in the spectacle "Coreografia de Cordel" (2004) of the Cia. de Dança do Palácio das Artes, based on the reference of the space in-between of Silviano Santiago (1978). With the reference on the idea that this space in-between is situated among the bordering limits of languages or disciplines already culturally structured and established, but often characterized by the emergence of a post-disciplinary expressiveness, here we lecture about the elements recognized in these boundaries between Dance and Theatre and its developments on the scene, related to the method Bailarino-Pesquisador-Intérprete (RODRIGUES, 1997), which guided the conception of the spectacle involved in this study. It has been recognized that these elements transit since the the preparation and creation of the scene, and they are scenic projections of this expressiveness that transforms as extensions of perceptions that permeate themselves in the body space, according to Jose Gil (2002). So, it doesn't matter here the designation of artistic gender or disciplinary reference to which may belong the spectacle, but the recognition of the elements that characterize a transdisciplinary creation and its development in post-disciplinary scenes, such as: a theatricality that projects in the cene the transgression of disciplinary relationships limits existing in the inventory spaces of the body (STRAZZACAPPA & MORANDI, 2006); a dramaturgy of bodys movements that can be observed in enlarged or reduced form on the character structuring and collaborative authoring of the spectacle; the performativity (FÉRAL, 2008) potentiated by the occupation of art non-places (AUGÉ, 2005). To become possible this sensitive look on this space in-between made by dilution of boundaries between scenic arts, observed in "Coreografia de Cordel", weve realized literature review, videographic and documentary analysis and interviews with the artists participants of the spectacle.